Role Of Zinc Supplementation In Thermal Burn Patients - DR.G.AMAR RAGHU NARAYAN; DR.SK.DEEPTHI (International Journal of Pharma and Bio Sciences, 2015)
Thermal injury of the skin is an oxidation process, associated with biological and metabolic alteration. It generates free radicals from various cellular population by a number of pathways. And modulation of generated free radicals activity with antioxidants may improve outcome. The objective of our study was to study the role of zinc supplementation on wound healing power in post burn patients. We have undergone a case control study on 40 patients we have assessed serum zinc levels, malonaldehyde, glutathione peroxidase levels at the time of admission and compare it after supplementation. There was a significant decrease in serum zinc levels at the time of admission but after supplementation there was an increase in serum zinc levels and improved antioxidant status as represented by elevation of natural antioxidant level (glutathione peroxidase).